Pitcher morphology and pitcher coloring of Nepenthes mirabilis Druce. from East Kalimantan, Indonesia - TRI HANDAYANI; JULISASI TRI HADIAH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Handayani T, Hadiah JT. 2019. Pitcher morphology and pitcher coloring of Nepenthes mirabilis Druce. from East Kalimantan, Indonesia. Biodiversitas 20: 2824-2832. The shape and color of Nepenthes pitchers play an important role in attracting preys. The terrestrial and aerial pitchers have different shapes in accordance with different preys they trap. This species has high potential as an ornamental plant due to the pitcher’s varied sizes, shapes and colors, which information of the wild species is inadequate. This study aimed to identify the morphological characters, size, and colors of pitcher and its parts (tendril, pitcher body, lid, peristome, wing) of N. mirabilis growing in the wild in East Kalimantan. Samples for morphological observation comprised 90 terrestrial pitchers and 90 aerial pitchers, and samples for pitcher coloring observation comprised 650 terrestrial pitchers and 650 aerial pitchers. The results showed that the shape of terrestrial pitchers were narrowly ovoid in the lower part and cylindrical toward the top. The aerial pitchers were infundibular in the lower part, narrowly ovoid in the middle then cylindrical toward the top. The highest percentage of terrestrial pitcher tendril’s color was green and the aerial pitcher tendril’s was reddish green. Most pitcher body’s color was green in the lower part and green with purple stripes in the upper part on both terrestrial and aerial pitchers (21.07% and 16.15%, respectively). The wing color of both pitchers was mostly purplish dark red which possessed the highest percentages (30.31% and 40.64%, respectively). The dominant peristome color of terrestrial pitcher was brownish dark red (26.15%), whereas that of the aerial pitcher was purplish dark red (44.19%). The lid color of both terrestrial and aerial pitchers was mostly purplish dark red (38.92% and 31.39% respectively). Bright color was mostly found on the peristome and lid. It was found on 85.38% of terrestrial pitcher’s peristome, 95.22% of terrestrial pitcher’s lid, 81.43% of aerial pitcher’s peristome, and 98.77% of aerial pitcher’s lid. The presence of green color on tendril, pitcher and its parts indicates its function in photosynthesis, whereas the presence of bright color shows its role in capturing preys.